Perovskite light absorption layer preparation method, perovskite cell device preparation method and product
By performing 2D/3D heterostructure modification and interface passivation treatment on the light absorption layer of perovskite solar cells, the problem of insufficient photoelectric conversion efficiency and stability of perovskite solar cells is solved, and higher photoelectric performance and longer service life are achieved.
Patent Information
- Application Number
- CN202411954354.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-21
AI Technical Summary
Existing perovskite solar cell devices have shortcomings in photoelectric conversion efficiency and stability, especially the quality and surface properties of the film have a great impact on device performance.
By spin-coating the perovskite precursor liquid and annealing twice, a perovskite light absorbing layer was formed, and the surface was modified with 3-piperidinide (PDN) to form a 2D/3D heterostructure, combined with the cleaning process of weak polar solvents, the stability and photoelectric properties of the perovskite film were enhanced.
The photoelectric conversion efficiency and stability of perovskite solar cells are significantly improved, and charge separation and transportation efficiency are improved by reducing carrier non-radiative recombination, thereby enhancing the interface passivation effect and extending the service life of the device.
Smart Images

Figure CN119677379A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of solar photovoltaic technology, and specifically to a method for preparing a perovskite light absorption layer, a method for preparing a perovskite cell device, and a product. Background Art
[0002] Perovskite structures are usually composed of organic cations and inorganic anions, showing efficient light absorption, high extinction coefficient and good carrier mobility. At the same time, the low exciton binding energy of perovskite enables it to effectively generate free carriers during the photoelectric conversion process, thereby improving the photoelectric conversion efficiency of solar cells. In addition, perovskite materials are suitable for solution preparation, which improves the simplicity and economy of production. According to the latest research progress, the certified efficiency of inverse perovskite solar cells has reached 26.7%. This shows that perovskite materials have great potential for application in photovoltaic technology.
[0003] In the device structure of perovskite solar cells, the perovskite film is not only a light absorption layer, but also the core of carrier generation and transport. The quality and surface properties of the film are extremely important to the device performance. Therefore, modifying the perovskite surface can effectively increase the carrier extraction rate. By reducing the charge accumulation at the interface, the non-radiative recombination of carriers caused by it can be reduced, thereby significantly improving the overall performance of the device.
[0004] In addition, interface modification materials can effectively passivate defects in perovskite films, block the intrusion of external factors such as moisture and oxygen, and the corrosion of metal electrodes, thereby enhancing the stability of the device. Therefore, developing a perovskite surface modification technology with simple process and low cost is still one of the important research directions for achieving efficient and stable perovskite solar cell preparation.
[0005] Currently, researchers are exploring a variety of modification strategies, including but not limited to the use of self-assembled monolayers, surface coatings, and chemical modifications. These methods aim to improve the electrical properties of perovskite films while maintaining their excellent optoelectronic properties. With the continuous advancement of perovskite materials and their device technologies, future photovoltaic applications will be more promising. Summary of the invention
[0006] In view of the problems in the prior art, the present invention provides a method for preparing a perovskite light absorption layer, a method for preparing a perovskite cell device and a product.
[0007] The present invention is achieved through the following technical solutions: A method for preparing a perovskite light absorbing layer comprises the following steps: S1, spin coating a perovskite precursor solution to obtain a perovskite wet film, and then annealing the perovskite wet film for the first time to obtain a perovskite thin film; S2, cooling the perovskite film to room temperature, spin coating or vapor deposition of the chelate molecule solution on the perovskite film, cleaning the surface of the perovskite film with a weak polar solution, and performing a second annealing to obtain a perovskite light absorption layer.
[0008] Preferably, in S1, the perovskite precursor solution is prepared by dissolving PbI2: (CH(NH2)2I+CsI) with a molar ratio of 1:1 in a polar solvent mixed with DMSO / DMF, sealing the mixed solution, and obtaining a clear perovskite precursor solution after sufficient dissolution. Preferably, the concentration of the perovskite precursor solution is 0.8-1.7M.
[0009] Preferably, during spin coating, the volume of the added perovskite precursor solution and the area of the perovskite film are in the range of 9.6 to 11 μL / cm 2 ; The thickness of the perovskite film is 700~800 nm.
[0010] Preferably, in S1, during the first annealing, the temperature is 100-150° C. and the time is 20-30 minutes.
[0011] Preferably, in S2, the chelating molecule solution is a 3-piperidinecarboxamide solution with a concentration of 5 mg / L; and the weak polar solution is isopropanol, chlorobenzene or n-butanol.
[0012] Preferably, in S2, during evaporation, the temperature is 100°C to 150°C, and the evaporation rate is 0.1 nm / s to 0.5 nm / s.
[0013] Preferably, in S2, during the second annealing, the temperature is 100-150°C and the time is 100-150°C.
[0014] A method for preparing a perovskite battery device comprises the following steps: S1, cleaning the FTO glass substrate; S2, preparing a hole transport layer on a FTO glass substrate; S3, preparing a perovskite light absorption layer on the hole transport layer using the perovskite light absorption layer preparation method; S4, preparing a PCBM electron transport layer on the perovskite light absorption layer; S5, preparing a bathocuproin BCP blocking layer on the PCBM electron transport layer; S6, vapor-depositing silver electrodes on the bathocuproin BCP barrier layer to obtain a perovskite battery device.
[0015] A product obtained according to the preparation method of the perovskite battery device.
[0016] Compared with the prior art, the present invention has the following beneficial effects: The present invention discloses a method for preparing a perovskite light absorption layer. The amino group in 3-piperidinecarboxamide (PDN) can form coordination with surface defects or under-coordinated metal ions (such as lead ions) to passivate the upper surface of the perovskite. At the same time, a modified weak polar solvent is used to clean the upper surface of the perovskite. While cleaning the excess PDN on the surface and the loosely bound perovskite or lead iodide particles, the drug PDN is added to form a 2D / 3D perovskite heterostructure structure on the original 3D perovskite, which can effectively improve the photoelectric conversion efficiency and stability of the perovskite solar cell. By introducing the 2D layer, the non-radiative recombination of carriers can be effectively reduced, and the charge separation and transport efficiency can be improved, thereby achieving higher photoelectric performance. In addition, the 2D layer can also increase the interface passivation effect on the perovskite surface, which helps to capture under-coordinated lead ions, further optimize the surface characteristics, and maximize the passivation function. Finally, the long-term stability of the device is significantly improved.
[0017] The present invention provides a method for preparing a perovskite battery device. The perovskite light absorption layer prepared by the above-mentioned perovskite light absorption layer preparation method is introduced into the perovskite battery device. The perovskite light absorption layer can effectively block the penetration of moisture and oxygen in the environment with a 2D / 3D structure, inhibit the diffusion of the Ag electrode into the perovskite layer, and enhance the overall stability of the device. Its excellent photoelectric performance, improved manufacturing process and relatively low cost will help promote the commercial application of perovskite solar cells. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 It is a flow chart of a method for preparing a perovskite light absorption layer of the present invention; Figure 2 It is a flow chart of a method for preparing a perovskite battery device of the present invention; Figure 3 It is a comparison chart of X-ray diffraction (XRD) of the perovskite film prepared by the method described in Example 1 of the present invention and the drug PDN spin-coated on glass; Figure 4 is a surface scan of an unmodified perovskite film in a comparative example; Figure 5 This is a surface scan of the perovskite film prepared by the method described in Example 1 of the present invention; Figure 6 This is a comparison chart of UV-Vis spectra of the perovskite film prepared by the method described in Example 1 of the present invention and the unmodified perovskite film surface; Figure 7 The dark current curves of the perovskite film prepared by the method described in Example 1 of the present invention and the unmodified perovskite film; Figure 8This is a comparison diagram of the surface steady-state fluorescence of the perovskite film prepared by the method described in Example 1 of the present invention and the unmodified perovskite film; Fig. 9 This is a comparison chart of the photoelectric conversion efficiency of the perovskite film prepared by the method described in Example 3 of the present invention and the unmodified perovskite film. DETAILED DESCRIPTION
[0019] The present invention is further described in detail below in conjunction with specific embodiments, which are intended to explain the present invention rather than to limit it.
[0020] The present invention discloses a method for preparing a perovskite light absorption layer, referring to Figure 1 , including the following steps: S1, spin coating the perovskite precursor solution to obtain a perovskite wet film, and then annealing the perovskite wet film for the first time to obtain a 700~800 nm perovskite film.
[0021] The preparation method of the perovskite precursor solution is as follows: PbI2: (CH(NH2)2I+CsI) with a molar ratio of 1:1 is dissolved in a polar solvent mixed with DMSO / DMF, the mixed solution is sealed, and after sufficient dissolution, a clear perovskite precursor solution with a concentration of 0.8~1.7M is obtained. During spin coating, the volume of the added perovskite precursor solution is related to the area of the perovskite film by 9.6~11 μL / cm 2 .
[0022] During the first annealing, the temperature is 100~150℃ and the time is 20~30 minutes.
[0023] S2, cooling the perovskite film to room temperature, spin coating or evaporating a chelating molecule solution with a concentration of 5 mg / L on the perovskite film, cleaning the surface of the perovskite film with a weak polar solution, and performing a second annealing to obtain a perovskite light absorption layer. In this process, the excess PDN on the surface and the loosely bound perovskite or lead iodide particles will be washed away, exposing more divalent lead ions. Due to the strong chelating effect between the chelating molecules and the lead ions, the more lead is exposed, the more chelating molecules are captured, and targeted passivation is achieved, maximizing the passivation effect.
[0024] The chelate molecule solution is 3-piperidinecarboxamide solution; the weak polar solution is isopropanol, chlorobenzene or n-butanol. During the second annealing, the temperature is 100-150°C and the time is 100-150°C.
[0025] During evaporation, the evaporation temperature is usually between 100°C and 150°C, and the evaporation rate is usually in the range of 0.1 nm / s to 0.5 nm / s. Pressure: During the evaporation process, the pressure is usually low vacuum (such as 1×10⁻ 5to ensure the purity of the evaporated material and the evaporation efficiency.
[0026] The present invention also discloses a method for preparing a perovskite battery device, referring to Figure 2 , including the following steps: S1, cleaning the FTO glass substrate; specifically, the fluorine-doped SnO2 (FTO) transparent conductive glass is ultrasonically cleaned using acetone, isopropanol, ethanol and ultrapure water for 30 minutes each, blown dry, and subjected to ultraviolet ozone for 10 to 15 minutes to remove surface organic impurities and increase the hydrophilicity of the FTO surface.
[0027] S2, preparing a hole transport layer on the FTO glass substrate; specifically, the hole transport layer can be nickel oxide, PTAA, PEDOT:PSS, etc., spin-coating a nanoparticle solution of the above materials onto the cleaned FTO substrate surface, and annealing at 100-150° C. for 20-30 minutes.
[0028] S3, preparing a perovskite light absorption layer on the hole transport layer using the perovskite light absorption layer preparation method; S4, preparing a PCBM electron transport layer on the perovskite light absorption layer; specifically, cooling the perovskite light absorption layer in S3 to room temperature, spin coating the PCBM solution on the surface of the perovskite light absorption layer to form an electron transport layer; the PCBM solution is a PCBM chlorobenzene solution. The relationship between the volume of the added PCBM solution and the area of the perovskite light absorption layer is 8~9.6 μL / cm 2 .
[0029] S5, preparing a 3-8 nm bathocuproin BCP barrier layer on the PCBM electron transport layer; specifically, spin coating or vapor deposition of the BCP solution on the surface of the electron transport layer to form the barrier layer, the solvent of the BCP solution is isopropanol.
[0030] S6, evaporate 80~120 nm silver electrode on the bathocuproin BCP barrier layer to obtain a perovskite battery device.
[0031] The present invention also discloses a product obtained according to the preparation method of the perovskite battery device. At room temperature, the light intensity of the solar simulator is increased to 100 mW / cm 2 (AM 1.5G), the efficiency of the perovskite battery device was tested.
[0032] Comparative Example Step 1, cleaning FTO glass substrate: Select fluorine-doped SnO2 (FTO) transparent conductive glass (2.5*2.5 cm 2 ), wipe off the surface impurities with dust-free paper, then use acetone, isopropanol, ethanol and ultrapure water for ultrasonic cleaning for 30 minutes each, blow dry, and treat with ultraviolet ozone for 10 minutes; Step 2, prepare the perovskite light absorption layer: dissolve PbI2: (CH(NH2)2I + CsI) with a molar ratio of 1:1 in a DMSO / DMF mixed solvent; seal the mixed solution, stir it thoroughly, and filter it to obtain a clear perovskite solution for use.
[0033] The perovskite precursor solution was uniformly coated on the surface of the glass substrate. The perovskite wet film was obtained by spin coating and then placed on a 100°C hot plate for 30 minutes to obtain an unmodified perovskite film. The relationship between the volume of the added perovskite precursor solution and the area of the perovskite film was 11 μL / cm 2 .
[0034] Example 1 Step 1, cleaning FTO glass substrate: Select fluorine-doped SnO2 (FTO) transparent conductive glass (2.5*2.5 cm 2 ), wipe off the surface impurities with dust-free paper, then use acetone, isopropanol, ethanol and ultrapure water for ultrasonic cleaning for 30 minutes each, blow dry, and treat with ultraviolet ozone for 10 minutes; Step 2, first, disperse nickel oxide nanoparticles in 1 mL of ultrapure water, ultrasonically disperse to form a nickel oxide nanoparticle aqueous solution, spin-coat the nickel oxide nanoparticle aqueous solution onto the surface of the FTO substrate, and anneal to obtain a nickel oxide hole transport layer.
[0035] Step 3, prepare the perovskite light absorption layer: dissolve PbI2: (CH(NH2)2I + CsI) with a molar ratio of 1:1 in a DMSO / DMF mixed solvent; seal the mixed solution, stir it thoroughly, and filter it to obtain a clear perovskite solution for use.
[0036] The perovskite precursor solution was uniformly coated on the surface of the nickel oxide substrate. The perovskite wet film was obtained by spin coating and then placed on a 100°C hot plate for 30 minutes to obtain a perovskite film. The relationship between the volume of the added perovskite precursor solution and the area of the perovskite film was 11 μL / cm 2 .
[0037] After the annealed perovskite film cools to room temperature, 3-piperidinecarboxamide (PDN) is spin-coated on the perovskite substrate and annealed at 100°C for 3 to 10 minutes. Then, a certain amount of isopropanol solvent is taken to clean the surface of the perovskite film and annealed at 100°C for 3 to 5 minutes to obtain a perovskite light absorption layer.
[0038] Step 4: Preparation of PCBM transport layer: The annealed perovskite light absorption layer was cooled to room temperature, and the PCBM chlorobenzene solution was spin-coated on the perovskite substrate to obtain the electron transport layer. The volume of the added PCBM solution was related to the area of the perovskite light absorption layer by 8 μL / cm 2 .
[0039] Step 5, preparation of BCP barrier layer: spin-coat the BCP solution on the surface of the PCBM layer to obtain a barrier layer with a thickness of 3 nm.
[0040] Step 6, Ag electrode evaporation: The prepared film was transferred into the evaporation chamber and 80 nm thick Ag electrode was deposited by thermal evaporation. The effective area of the mask was 0.09 cm 2 .
[0041] The photoelectric conversion efficiency of the perovskite cell device prepared in Example 1 was tested: at room temperature, a Keithley 2400 solar simulator was used at a light intensity of 100 mW / cm 2 The battery efficiency was tested under (AM 1.5G) conditions with a voltage sweep range of 1.5 V to -0.1 V and -0.1 V to 1.5 V.
[0042] Figure 3 , 4 The X-ray diffraction diagram of the perovskite film before and after optimization. It can be seen from the figure that compared with the control group (CT), a new phase appeared at 8.7° in the optimized (PDN) film, which is presumed to be a 2D perovskite. In order to prove that it is not the phase of the drug itself, PDN was further spin-coated on pure glass. It can be seen from the figure that the same new phase did not appear at 8.7°, further confirming that PDN reacted with the original 3D perovskite to generate 2D perovskite.
[0043] Figure 5 These are scanning electron microscope images of the perovskite film before and after optimization. From the figure, we can see that compared with the control group (CT), layered 2D perovskite appears on the surface of the optimized (PDN) 3D perovskite.
[0044] Figure 6 The UV absorption spectra of the perovskite film before and after optimization. It can be seen from the figure that compared with the control group (CT), the absorption peak of the optimized (PDN) film in the UV region is significantly enhanced, indicating that the optimized film has improved its ability to absorb UV light. This means that the optimized perovskite film can more effectively absorb the high-energy UV components in sunlight, thereby improving its photoelectric conversion efficiency.
[0045] Figure 7 The dark current diagram of the perovskite film before and after optimization shows that the dark current value of the optimized film (PDN) is lower than that of the control group (CT), indicating that the current leakage of the optimized film is reduced under no light conditions. This feature helps to improve the stability and efficiency of the device and reduce energy loss.
[0046] Figure 8This is the fluorescence spectrum of the perovskite film before and after optimization. It can be seen from the figure that compared with the control group (CT) device, the optimized (PDN) device has a higher luminescence intensity, indicating that the non-radiative recombination on the surface of the optimized film is suppressed, proving the inhibitory effect of the optimization process on the surface defects of the perovskite film.
[0047] Example 2 Step 1, cleaning FTO glass substrate: Select fluorine-doped SnO2 (FTO) transparent conductive glass (2.5*2.5 cm 2 ), wipe off the surface impurities with dust-free paper, and then use acetone, isopropanol, ethanol and ultrapure water for ultrasonic cleaning for 30 minutes each, blow dry, and treat with UV ozone for 15 minutes.
[0048] Step 2: First, nickel oxide nanoparticles are dispersed in 1 mL of ultrapure water, and ultrasonically dispersed to form an aqueous solution of nickel oxide nanoparticles. The aqueous solution of nickel oxide nanoparticles is spin-coated onto the surface of the FTO substrate, and annealed to obtain a nickel oxide hole transport layer.
[0049] Step 3, preparing a perovskite light absorption layer: dissolving PbI2:CH(NH2)2I:CsI in a molar ratio of 1:0.98:0.02 in a DMSO / DMF mixed solvent; sealing the mixed solution, stirring it sufficiently, and filtering it to obtain a clear perovskite solution for later use; The perovskite precursor solution was uniformly coated on the surface of the nickel oxide substrate; the perovskite wet film was obtained by spin coating and then placed on a 110°C hot plate for 30 minutes to obtain a perovskite film. The relationship between the volume of the added perovskite precursor solution and the area of the perovskite film was 9.6 μL / cm 2 ; Surface modification of perovskite film: After the annealed perovskite film cools to room temperature, 3-piperidinecarboxamide (PDN) is evaporated on the perovskite substrate. Then, a certain amount of n-butanol is taken to clean the surface of the perovskite film, and annealed at 100°C for 3 to 10 minutes to obtain a perovskite light absorption layer.
[0050] Step 4: Preparation of PCBM transport layer: The annealed perovskite light absorption layer was cooled to room temperature, and the PCBM chlorobenzene solution was spin-coated on the perovskite substrate to obtain the electron transport layer. The relationship between the volume of the added PCBM solution and the area of the perovskite light absorption layer was 9.6 μL / cm 2 .
[0051] Step 5, preparation of BCP barrier layer: vacuum thermal evaporation of BCP solution on the PCBM surface to obtain a BCP barrier layer with a thickness of 8 nm.
[0052] Step 6, Ag electrode evaporation: The prepared film was transferred into the evaporation chamber and a 100 nm thick Ag electrode was deposited using thermal evaporation. The effective area of the mask was 0.09 cm 2 .
[0053] The photoelectric conversion efficiency of the perovskite cell device prepared in Example 2 was tested: at room temperature, a Keithley 2400 solar simulator was used at a light intensity of 100 mW / cm 2 The battery efficiency was tested under (AM 1.5G) conditions with a voltage sweep range of 1.5 V to -0.1 V and -0.1 V to 1.5 V.
[0054] Example 3 Step 1, cleaning the FTO glass substrate: select fluorine-doped SnO2 (FTO) transparent conductive glass (2.5*2.5 cm2), wipe the surface impurities with dust-free paper, and then use acetone, isopropanol, ethanol and ultrapure water for ultrasonic cleaning for 30 minutes each, blow dry, and treat with ultraviolet ozone for 12 minutes; Step 2, first, disperse nickel oxide nanoparticles in 1 mL of ultrapure water, ultrasonically disperse to prepare a nickel oxide nanoparticle aqueous solution, spin-coat the nickel oxide nanoparticle aqueous solution onto the surface of the FTO substrate, and anneal to obtain a nickel oxide hole transport layer; Step 3, preparing a perovskite light absorption layer: dissolving PbI2: (CH(NH2)2I + CsI) in a molar ratio of 1:1 in a DMSO / DMF mixed solvent; sealing the mixed solution, stirring it sufficiently, and filtering it to obtain a clear perovskite solution for later use; The perovskite precursor solution was uniformly coated on the surface of the nickel oxide substrate; the perovskite wet film was obtained by spin coating and then placed on a 150°C hot plate for 15 minutes to obtain a perovskite film. The relationship between the volume of the added perovskite precursor solution and the area of the perovskite film was 10 μL / cm 2 ; After the annealed perovskite film cools to room temperature, 3-piperidinecarboxamide (PDN) is spin-coated on the perovskite substrate and annealed at 100°C for 3 to 10 minutes. Then, a certain amount of isopropanol solvent is taken to clean the surface of the perovskite film and annealed at 100°C for 3 to 5 minutes to obtain a perovskite light absorption layer.
[0055] Step 4: Preparation of PCBM transport layer: The annealed perovskite light absorption layer was cooled to room temperature, and the PCBM chlorobenzene solution was spin-coated on the perovskite substrate to obtain the electron transport layer. The relationship between the volume of the added PCBM solution and the area of the perovskite light absorption layer was 9 μL / cm 2 .
[0056] Step 5, preparation of BCP barrier layer: spin-coat the BCP solution on the surface of the PCBM layer to obtain a barrier layer with a thickness of 5 nm.
[0057] Step 6, Ag electrode evaporation: The prepared film was transferred into the evaporation chamber and a 120 nm thick Ag electrode was deposited using thermal evaporation. The effective area of the mask was 0.09 cm 2 .
[0058] The photoelectric conversion efficiency of the perovskite cell device prepared in Example 3 was tested: at room temperature, a Keithley 2400 solar simulator was used at a light intensity of 100 mW / cm 2 (AM 1.5G) conditions to test battery efficiency, such as Fig. 9 As shown, it can be seen that compared with the control group (CT) device, the optimized (PDN) device achieved higher photoelectric conversion efficiency.
[0059] The above description is only a preferred embodiment of the present invention and is not intended to impose any limitation on the technical solution of the present invention. Those skilled in the art should understand that, without departing from the spirit and principles of the present invention, the technical solution can also be subjected to several simple modifications and substitutions, and these modifications and substitutions are also within the scope of protection covered by the claims.
Claims
1. A method for preparing a perovskite light absorbing layer, characterized in that: The following steps are involved: S1, spin coating a perovskite precursor solution to obtain a perovskite wet film, and then annealing the perovskite wet film for the first time to obtain a perovskite thin film; S2, cooling the perovskite film to room temperature, spin coating or vapor deposition of the chelate molecule solution on the perovskite film, cleaning the surface of the perovskite film with a weak polar solution, and performing a second annealing to obtain a perovskite light absorption layer.
2. The method for preparing a perovskite light absorbing layer according to claim 1, characterized in that: In S1, the perovskite precursor solution is prepared by dissolving PbI2: (CH(NH2)2I+CsI) with a molar ratio of 1:1 in a DMSO / DMF mixed polar solvent, sealing the mixed solution, and obtaining a clear perovskite precursor solution after sufficient dissolution.
3. The method for preparing a perovskite light absorbing layer according to claim 2, characterized in that: The concentration of the perovskite precursor solution is 0.8~1.7M.
4. The method for preparing a perovskite light absorbing layer according to claim 1, characterized in that: During spin coating, the relationship between the volume of the added perovskite precursor solution and the perovskite film area is 9.6~11 μL / cm 2 ; The thickness of the perovskite film is 700~800nm.
5. The method for preparing a high-efficiency inverse perovskite solar cell with a 2D / 3D heterojunction based on interface modification on perovskite according to claim 1, characterized in that: In S1, during the first annealing, the temperature is 100-150°C and the time is 20-30 minutes.
6. The method for preparing a perovskite light absorbing layer according to claim 1, characterized in that: In S2, the chelating molecule solution is a 3-piperidinecarboxamide solution with a concentration of 5 mg / L; the weak polar solution is isopropanol, chlorobenzene or n-butanol.
7. The method for preparing a perovskite light absorbing layer according to claim 1, characterized in that: In S2, during evaporation, the temperature is 100°C ~150°C, and the evaporation rate is 0.1 nm / s ~ 0.5 nm / s.
8. The method for preparing a perovskite light absorbing layer according to claim 1, characterized in that: In S2, during the second annealing, the temperature is 100~150℃ and the time is 100~150℃.
9. A method for preparing a perovskite battery device, characterized in that: The following steps are involved: S1, cleaning the FTO glass substrate; S2, preparing a hole transport layer on a FTO glass substrate; S3, preparing a perovskite light absorption layer on the hole transport layer using the method for preparing a perovskite light absorption layer according to any one of claims 1 to 8; S4, preparing a PCBM electron transport layer on the perovskite light absorption layer; S5, preparing a bathocuproin BCP blocking layer on the PCBM electron transport layer; S6, vapor-depositing silver electrodes on the bathocuproin BCP barrier layer to obtain a perovskite battery device.
10. A product obtained by the method for preparing a perovskite battery device according to claim 9.